2018
DOI: 10.1002/jcb.27465
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and proteomic profiling of pancreatic cancer‐derived serum exosomes

Abstract: Pancreatic cancer (PC) is one of the most lethal cancers known worldwide, and its prognosis is poor in most patients. Exosomes are nanosized extracellular vesicles, which are released from various cell types. They are involved in cellular communication. The diagnosis and treatment of PC were improved substantially with exosomes. In this study, we isolated PC-derived exosomes and investigated their proteomic profile. Then, we conducted bioinformatic analysis on proteomic data. Differential ultracentrifugation w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 43 publications
2
25
0
Order By: Relevance
“…Notably, serum-derived EV-associated LBP (Lipopolysaccharide-binding protein) has previously been shown to be elevated in PDAC cases as compared to healthy controls. Consistent with this study, we also observed that LBP is elevated in EVs of PDAC cases as compared to controls, thus providing independent validation [29].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Notably, serum-derived EV-associated LBP (Lipopolysaccharide-binding protein) has previously been shown to be elevated in PDAC cases as compared to healthy controls. Consistent with this study, we also observed that LBP is elevated in EVs of PDAC cases as compared to controls, thus providing independent validation [29].…”
Section: Discussionsupporting
confidence: 90%
“…We note that a novel component of this study in relation to other studies, which have similarly evaluated utility of EV-associated protein cargo for early detection or prognostication [29,30], is the direct comparison protein features in plasma-derived EVs versus unfractionated plasma from the same individual for utility in distinguishing case from control. This approach enables us to address a fundamental question and conclude that there are indeed EV-associated features that exhibited improved classifier performance specifically in the plasma sEV compartment.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that the ultrastructure and size of plasma exosomes complied with the typical morphology of exosomes [31,32]. The surface markers of exosomes mainly included CD9, CD63, CD81, CD82, HSP27, HSP90, TSG101 and ALIX [33]. Here, the presence of exosomes was con rmed with the detection of CD63 and TSG101, and the purity of exosomes was con rmed by the absence of Calnexin.…”
Section: Discussionsupporting
confidence: 56%
“…At this point, a supernatant filtration is sometimes carried out to remove particles larger than 200 nm. Finally, the recovery of exosomes is performed by ultracentrifugation at 100,000–200,000× g for hours [ 80 , 81 , 82 ] and the pellet is washed by resuspension with PBS and centrifuged again to remove contaminants and improve the purity.…”
Section: Proteomic Methodsmentioning
confidence: 99%